An Explorer's Guide to the Nether : Lost Minecraft Journals #2 - Morgan, Winter (New York : Sky Pony Press, 2015)
Treasure hunters Harriet, Jack, and Toby discover the lost journals of William, a legendary explorer who has gone missing, and use them to reach a secret section of the Nether, only to discover two sinister treasure hunters are trailing them.
"An unofficial Minecrafter's adventure"--Cover.
Keywords: Adventure and adventurers -- Fiction; Diaries -- Fiction; Minecraft (Game) -- Fiction; Fantasy; Diaries -- Fiction; Minecraft (Game).) -- Fiction; Adventure fiction; Fantasy fiction